Overexpression of the Cochaperone CHIP Enhances Hsp70-Dependent Folding Activity in Mammalian Cells - Kampinga, Harm H. (American Society for Microbiology, 2003)
CHIP is a cochaperone of Hsp70 that inhibits Hsp70-dependent refolding in vitro. However, the effect of altered expression of CHIP on the fate of unfolded proteins in mammalian cells has not been determined. Surprisingly, we found that overexpression of CHIP in fibroblasts increased the refolding of proteins after thermal denaturation. This effect was insensitive to geldanamycin, an Hsp90 inhibitor, and required the tetratricopeptide repeat motifs but not the U-box domain of CHIP. Inhibition of Hsp70 chaperone activity abolished the effects of CHIP on protein folding, indicating that the CHIP-mediated events were Hsp70 dependent. Hsp40 competitively inhibited the CHIP-dependent refolding, which is consistent with in vitro data indicating that these cofactors act on Hsp70 in the ATP-bound state and have opposing effects on Hsp70 ATPase activity. Consistent with these observations, CHIP overexpression did not alter protein folding in the setting of ATP depletion, when Hsp70 is in the ADP-bound state. Concomitant with its effects on refolding heat-denatured substrates, CHIP increased the fraction of nascent chains coimmunoprecipitating with Hsc70, but only when sufficient ATP was present to allow Hsp70 to cycle rapidly. Our data suggest that, consistent with in vitro studies, CHIP attenuates the Hsp70 cycle in living cells. The impact of this effect on the fate of unfolded proteins in cells, however, is different from what might be expected from the in vitro data. Rather than resulting in inhibited refolding, CHIP increases the folding capacity of Hsp70 in eukaryotic cells.